Prognostic value of ST2 biomarkers in hypertonic disease patients on the background of the chronic obstructive pulmonary disease - Kraydashenko, O.; Tyaglaya, O. (Journal of Education, Health and Sport, 2021)
Introduction. Scientific research by domestic and foreign scientists and many years of clinical experience suggests that in patients with chronic obstructive pulmonary disease (COPD) a combination with arterial hypertension (AH) were often observed. Soluble form of ST2 protein of the patients is involved in certain inflammatory diseases and in the paracrine system of protection of the heart and lungs as marker, that determines the prognosis in patients with heart and lung deficiency and predicts the death of the patient during the year. The purpose of this study was to evaluate the expression of ST2 protein in patients with arterial hypertension on the background of chronic obstructive pulmonary disease. Materials and methods. In 23 patients were diagnosed arterial hypertension stage II and COPD stage II without clinically significant concomitant disease, with an average age 51.72 ± 1.22 years (49.33-54.09) (gender composition: 22 males and 1 female), the smoking status is comparable to COPD patients, 18 patients with AH of both sexes aged from 33 to 67 years (mean age 50.74 ± 1.49 years (47.81-53.76), male / female ratio 17 / 83%), stage II of the arterial hypertension with the level of I-III degree of hypertension, different cardiovascular risk, without adequate systematic antihypertensive therapy and 18 patients with COPD stage II, mean age 50.32 ± 0.99 years (48.22-52.16) (gender composition: 14 males and 4 females), duration of the disease 7.52 ± 1.14 years. 80% of active smokers, the index of bacon-years 17.23 ± 2.69 years, the harmful professional factors (industrial) indicated 23.53%. Participants expressed their willingness to be included in medical research. Research results. The obtained data indicate that the lowest level of expression of ST2 protein was detected in patients with hypertension without concomitant pathology – 21.05 ± 2.12 ng/mL, which is in 11.78% lower than in patients with COPD without concomitant pathology (23,53 ± 1.8 ng/mL). The highest expression ​​of ST2 protein were demonstrated in patients with comorbid pathology group with COPD on the background of AH – 33.01 ± 6.25 ng/mL, which is in 56.82% higher compared with patients with AH, and in 40.29% higher than analogous marker in patients with monopathology in the form of COPD. In the group of COPD patients with a high level of ST2 (more than 30 ng / ml), significantly more negatively controlled negative cardiovascular predictors, such as the presence of left ventricular hypertrophy (χ2 = 7.61 at p = 0.006) and sympathetic balance disturbances according to the LF / HF index (χ2 = 4.72 at p = 0.03) and ST2 elevation was reliably associated not only with extrapulmonary prognostic factors, but also with a decrease in FEV1 of less than 50% (χ2 = 5.45 at p = 0.02). Conclusions. Patients of the experimental group with comorbid pathology AH and COPD had the most significant increasing level of ST2 protein as unfavorable prognosis marker compared to the groups of patients without combination of this pathology.